Observations of E region field-aligned irregularities just outside the equatorial electrojet region - Chau Chong Shing, Jorge Luis (2000)
We have used the Piura VHF radar (5° 12’S, 80°38’W, ~7.5°N dip latitude), just outside the equatorial electrojet region, in northern Perú (see Figure 1) to gather echoes from 3-m E region field-aligned irregularities (FAI). Our observations are based on short campaigns of few consecutive days taken since 1995 at different times of the year. E region FAIs over Piura are confined to the 95-120 km altitude and present spectral characteristics similar to type 2 equatorial electrojet (EEJ) echoes. However, despite of being at only 7°N dip latitude, they appear mainly at nighttime and early morning, and thus do not present a temporal similarity to the EEJ. We observe the existence of two well-defined types of echoes: 1) lower E region echoes (95-105 km), and upper E region echoes (105-120 km). The lower echoes present a layering characteristic while the upper layer is more structured. In this latter region, the so-called quasiperiodic (QP) echoes have been observed with positive, vertical, and negative slopes and their characteristics are compared to those observed at mid latitudes. In addition, a relationship between concurrent E region irregularities over Piura and F region irregularities over Piura and Jicamarca is presented.